Role of potential bioactive metabolites from traditional Chinese medicine for type 2 diabetes mellitus: An overview - Li, Xiang; Geng-Ji, Jia-Jia; Quan, Yun-Yun; Qi, Lu-Ming; Sun, Qiang; Huang, Qun; Jiang, Hai-Mei; Sun, Zi-Jian; Liu, Hong-Mei; Xie, Xin (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) is a metabolic disease with persistent hyperglycemia primarily caused by insulin resistance (IR). The number of diabetic patients globally has been rising over the past decades. Although significant progress has been made in treating diabetes mellitus (DM), existing clinical drugs for diabetes can no longer fully meet patients when they face complex and huge clinical treatment needs. As a traditional and effective medical system, traditional Chinese medicine (TCM) has a unique understanding of diabetes treatment and has developed many classic and practical prescriptions targeting DM. With modern medicine and pharmacy advancements, researchers have discovered that various bioactive metabolites isolated from TCM show therapeutic on DM. Compared with existing clinical drugs, these bioactive metabolites demonstrate promising prospects for treating DM due to their excellent biocompatibility and fewer adverse reactions. Accordingly, these valuable metabolites have attracted the interest of researchers worldwide. Despite the abundance of research works and specialized-topic reviews published over the past years, there is a lack of updated and systematic reviews concerning this fast-growing field. Therefore, in this review, we summarized the bioactive metabolites derived from TCM with the potential treatment of T2DM by searching several authoritative databases such as PubMed, Web of Science, Wiley Online Library, and Springer Link. For the convenience of readers, the content is divided into four parts according to the structural characteristics of these valuable compounds (flavonoids, terpenoids, alkaloids, and others). Meanwhile, the detailed mechanism and future directions of these promising compounds curing DM are also summarized in the related sections. We hope this review inspires increasingly valuable and significant research focusing on potential bioactive metabolites from TCM to treat DM in the future.